This action might not be possible to undo. Are you sure you want to continue?
Basic Calculus 1. 2. 3. 4. 5. Functions Linear Functions Quadratic Functions Exponential Functions Logarithmic Functions
1
2
Functions
1
Functions
Example: y = x + 2
1
A function is a rule that assigns to each input number exactly one output number. The set of all input numbers to which the rule applies is called the domain of the function. The set of all output numbers is called the range. A variable that represents input numbers for a function is called an independent variable. A variable that represents output numbers is called a dependent variable because its value depends on the value of the independent variable.
3
defines y as a function of x. It gives the rule: Add 2 to x. This rule assigns to each input x exactly one output x + 2, which is y. Thus if x = 1, then y = 3; if x = 4, then y = 2. The independent variable is x and the dependent variable is y.
4
Functions
1
Functions
Example: To find f(3), which is the output corresponding to the input 3, we replace each x in f(x) = x + 2 by 3: f(3) = 3 + 2 = 5 input = 8 f(8) = 8 + 2 = 10 (output) input = 4 f(4) = 4 + 2 = 2 (output)
1
Usually, the letters f, g, h, F, G and so on are used to represent function rules. If y = x + 2 defines y as a function of x, then we say that f is the function of x, and we can write it as f(x) = x + 2 f(x), which is read “f of x”, means the output number in the range of f that corresponds to the input number x in the domain.
5
6
Domain of a function
1
Domain of a function
Example 1: Find the domain for function x f(x) =
1
Unless otherwise stated, the domain consists of all real numbers for which the rule of the function makes sense, that is, it gives function values that are real numbers. 1 For example, suppose h(x) =
x2 − x − 2
x−6
–x–2=0 (x – 2)(x + 1) = 0 x = 2, 1. Therefore, the domain of f is all real numbers except 2 and –1
8
x2
Here any real number can be used for x except 6 because the denominator is 0 when x is 6. Thus the domain h is understood to be all real numbers except 6.
7
Finding Domain and Function values
1
Finding a Difference Quotient
If f(x) = x2, find f ( x + h) − f ( x ) Solution: The expression is h referred to as a difference quotient. Here the numerator is a difference of function values. f ( x + h ) − f ( x ) = ( x + h) 2 − x 2
1
Let g(x) = 3x2 – x + 5. Any real number can be used for x, so the domain of g is all real numbers.
Find g(z)
Solution : Replacing each x in g(x) = 3x2 – x + 5 by z gives
h f ( x + h) − f ( x)
Find g(r2)
g(z) = 3(z)2 – z + 5 = 3z2 – z + 5
Solution: Replacing each x in g(x) = 3x2 – x + 5 by r2 gives
h
Find g(x + h)
g(r2)
=3
(r2)2
–
r2
+5=
3r4

r2
+5
= x + 2hx + h 2 − x 2 = 2hx + h 2 = h( 2 x + h) = 2x + h
h
h
Solution: g(x + h) = 3(x+h)2 – (x + h) + 5
= 3(x2 + 2hx + h2) – x – h + 5 =3x2 + 6hx + 3h2 – x – h + 5
h
9
h
10
Combination of Functions
1
Combination of Functions
1
There are different ways of combining two functions to create a new function.
Suppose f and g are the functions given by
In general, for any functions f and g, there are 4 types of combination:
Sum (f + g): (f + g)(x) = f(x) + g(x) Difference (f – g): (f – g)(x) = f(x) – g(x) Product (fg): (fg)(x) = f(x).g(x) Quotient ( ) :
f(x) = x2
and g(x) = 3x
Adding f(x) and g(x) gives
This operation defines a new function called the sum of f and g, denoted f + g. Its function value at x is f(x) + g(x). That is,
f(x) + g(x) = x2 + 3x
(f + g)(x) = f(x) + g(x) = x2 + 3x
f g
f g
(x) =
f(x) g(x)
12
11
Combination of Functions
1
Combination of Functions
1
Example If f(x) = 3x – 1 and g(x) = x2 + 3x find a. (f + g)(x) b. (f – g)(x) c. (fg)(x) d. f (x) g
13
Solution: a) (f + g)(x)= 3x – 1 + x2 + 3x = x2+ 6x + 1 b) (f – g)(x)=3x – 1 – (x2 + 3x) =3x – 1 – x2  3x = – x2 – 1 c) (fg)(x) = (3x – 1)(x2 + 3x) = 3x3 + 9x2 x2 3x = 3x3 + 8x2  3x f (x) = (3x – 1) d) g (x2 + 3x)
14
Linear Function
2
Linear Function
2
Definition: A function f is a linear function if and only if f(x) can be written in the form f(x) = mx + c, where m and c are constants and m ≠ 0
Suppose that f(x) = mx + c is a linear function and we let y = f(x). Then y = mx + c, which is an equation of a straight line with slope a and yintercept b. Thus the graph of a linear function is a straight line. We say that the function f(x) = mx + c has a slope m
15
16
Slope of a line
2
Slope of a line
Example: Find the slope of a line passing through (2,3) and (4,4) Solution: m=4–3 4–2 =1 2
2
Definition Let (x1, y1) and (x2,y2) be two different points on a nonvertical line. The slope of the line is the number m given by y − y1 m = ∆y = vertical.change = 2 x 2 − x1 horizontal.change ∆x
17
18
Equations of Lines
2
Equations of Lines
2
If we know a point on a line and the slope of the line, we can find an equation whose graph is that line. Suppose that line L has a slope m and passes through the point (x1,y1). If (x,y) is any other point on L, we can find an algebraic relationship between x and y. Using the slope formula on the point (x1,y1) and (x, y) gives
y  y1 = m(x – x1)
19
y − y1 = m x − x1
Example: Find and equation of the line passing through (3 , 8) and (4, 2). Solution: First, find the slope of the line. y − y1 m= = −2−8 = − 10 x − x1 7 4 − (−3)
20
Equations of Lines
2
Finding the slope and yintercept of a Line
2
Secondly, use a pointslope form with (3, 8) as (x1,y1) gives y–8=
− 10 (x – (3)) 7 − 10 30 y = x+8 7 7 26 − 10 y = x+ or 10x +7y –26 = 0 7 7
21
Example: Find the slope and yintercept of the line with equation y = 5(32x) Solution: y = 5(32x) y = 15 – 10x rewrite in the form of y= mx + c y = 10x +15 Thus m = 10 and c = 15, so the slope is –10 and the yintercept is 15.
22
Parallel and Perpendicular line
Parallel Lines
2
Parallel and Perpendicular line
Example
2
Two lines are parallel if and only if they have the same slope or are vertical.
Perpendicular lines
Two lines with slope m1 and m2 are perpendicular to each other if, and only if, 1 m1 = 
Figure below shows two lines passing through (3, 2). One is parallel to the line y = 3x + 1 and the other is perpendicular to it. Find equations of these lines.
m2
23
24
Parallel and Perpendicular line
2
Parallel and Perpendicular line
Solution: b) The slope of a line perpendicular to y = 3x + 1 must be  1 3 . Using a point –slope form, we get y  y1 = m(x – x1) y  (2) =  1 3(x – 3) y + 2 =  1 3x + 1 y =  1 3x – 1
2
Solution: a) The slope of y = 3x + 1 is 3. Thus the line through (3 , 2) that is parallel to y = 3x + 1 also has slope 3. Using a pointslope form, we get y  y1 = m(x – x1) y  (2) = 3 (x – 3) y + 2 = 3x – 9 y = 3x  11
25
26
Intercepts and Graph
2
Intercepts and Graph
Find the x and y intercepts of y = x2 + 2x – 3 i) Setting y = 0 and solving for x gives 0 = x2 + 2x – 3 0 = (x + 3)(x – 1) x = 3, 1 Thus the xintercepts are (3,0) and (1,0) ii) Setting x = 0 and solving for y gives y = 02 +2(0) –3 y = 3 Thus the yintercepts is (0,3)
2
An xintercepts of the graph of an equation in x and y is a point where the graph intersects the xaxis. A yintercept is a point where the graph intersects the yaxis. To find the xintercepts of the graph of an equation in x and y, we first set y = 0 and solve the resulting equation for x. To find the yintercepts, we first set x = 0 and solve for y.
27
Example:
28
Intercepts and Graph
Example
2
Middle point between two coordinates on a straight line
2
Find the intersect point between two lines, x + 3y = 9 and 3x – y –7=0 x + 3y = 9 ………………………….(1) Solution: 3x – y – 7 = 0………………………(2) From (1), x = 9 – 3y Replace x into equation (2), which gives Replace y in x which gives, 3(9 – 3y) – y – 7 = 0 27 – 9y – y – 7 = 0 x = 9 – 3(2) = 3 20 – 10y = 0 10y = 20 y=2 Thus the intersect point between two lines, x + 3y = 9 and 3x – y – 7 = 0 is (3,2)
The Middle point between two coordinate A(x1, y1) and B(x2,y2) is given as,
x +x 2
1
2
,
y+y 2
1
2
Find the middle point between A (2,4) and B (6,10) . Solution: 2+6 4 +10 = (4,7) ,
Example
2
2
29
30
Distance between two points
The distance between A(x1, y1) and B(x2,y2) gives
1
2
GRAPHING LINEAR FUNCTIONS
a. Graph f(x) = 2x + 1 m = 2, c = 1
f(x) 1 x f(x) = 2x + 1
2
x − x2 + y1 − y2
2
2
Example: Find the distance between (1,4) and (2,5). Solution: 2 2 = 1− (−2) + 1− 5 2 2 = 3 + − 4 = 25 =5
31
32
GRAPHING LINEAR FUNCTIONS
b. Graph g(t) =
2
Quadratic Functions
3
15  2t 3
Notice that g is a linear function because we can express it in the form g(t) = at + b;
g(t) =
g(t) 5
15  2t 15 2t 2 = = t +5 3 3 3 3
15  2t g(t) = 3
t
2 m= , c=5 3
A function is a quadratic function if and only if f(x) can be written in the form f(x) = ax2 + bx + c, where a, b, and c are constants and a ≠ 0
33
34
Quadratic Functions
For example the functions f(x) = x2 – 3x + 2 and f(t) = 3t2 are quadratic. 1 However, g(x) =
3
Quadratic Functions Graph
3
x2
The graph of the quadratic function y = f(x) = ax2 + bx + c is called a parabola and has a shape like the curves in the following figure.
y
is not quadratic because it cannot be written in the form g(x) = ax2 + bx + c
35
x
36
Quadratic Functions Graph
If a > 0 , the graph extends upward indefinitely and we say the parabola opens upward.
y
3
Quadratic Functions Graph
3
If a < 0, the parabola opens downward.
y
a > 0 c > 0
a < 0 c > 0
Each parabola is symmetric about vertical line, called the axis of symmetry of the parabola. The figure below shows a point called vertex, where the axis cuts the parabola. If a > 0, the vertex is the lowest point of the parabola. This means that f(x) has a minimum value at this point
y
x y y
x
If a < 0, the vertex is the highest point of the parabola. This means that f(x) has a maximum value at this point
y
axis of symmetry
x
vertex (maximum value)
x
x
37
x
vertex (minimum value)
axis of symmetry 38
Vertex
The formula for vertex is given by:
3
yintercept
3
− b − b Vertex = 2a , f 2 a
The point where the parabola y = ax2 + bx + c intersects the yaxis (that is the yintercept) occurs when x = 0. The ycoordinate of this point is c, so the yintercept is (0,c).
39
40
xintercept
The xintercept occur when y = 0. There are 3 types of xintercepts: For a > 0:
y y y
3
xintercept
For a < 0:
y x y x y
3
x
x
x
x
1 solution for x b24ac = 0
2 solution for x b24ac > 0
no solution/ no xintercepts b24ac < 0
41
1 solution for x b24ac = 0
2 solution for x b24ac > 0
no solution/ no xintercepts b24ac < 0
42
xintercept
To find the xintersects,
(i) Factorization − b ± b 2 − 4ac (ii) Quadratic Formula, x = 2a
3
xintercept
3
b2 – 4ac is called source of an equation. If a and b is a source for a quadratic equations, the equation will be: (x – a)(x – b) = 0 or x2 – (a + b)x + ab = 0
43
Example Find p and q if x = 1 and x = 4 for the equation x2 + px + q = 0 Solution: x2 + px + q = x2 – (a + b)x + ab = 0 = x2 – (1 + 4)x + (1)(4) = 0 = x2 – 5x + 4 = 0
44
Quadratic Functions Graph: Example
Example: Graph the quadratic function y = f(x) = x2 – 4x + 12 Solution: Step 1: Here a = 1, b = 4, and c = 12. Since a < 0, the parabola opens downward and thus has a highest point (maximum value)
3
Quadratic Functions Graph: Example
Step 2: (a = 1, b = 4) Formula to find vertex is
 b  (4) = = 2 2a 2(1)
3
−b 2a ,
− b f 2a
f(
The xcoordinate of the vertex is (2,16)
45
b ) = f( 2 )= (2) 2 4(2)+12 2a = 4+8+12 = 16
46
Quadratic Functions Graph: Example
3
Quadratic Functions Graph: Example
Step 4: draw the function graph
y
16 12 8 4 6 4 2
3
Step 3: yintercept: when x = 0 y = f(x) = x2 – 4x + 12 = 0 – 0 + 12 = 12 then yintercept is (0,12) xintercept: when y = 0 y = f(x) = x2 – 4x + 12 0 =  (x2 + 4x + 12) 0 =  (x + 6)(x – 2) Thus x = 6 or x = 2, so the xintercepts are (–6,0) and (2,0) 47
x
4 8 2
48
Exponential Function
The function f defined by f(x) = bx
4
Exponential Function
Example: 1. 2. 3. 4. f(x) = 3x f(t) = 0.12t f(x) = ex (original exponent, e ≈ 2.71828 ) If the base is 2 and x = 4, the function value f(4) will equal 16
4
Where b > 0, b ≠ 1, and the exponent x is any real number, is called an exponential function with base b
49
50
Rules for exponent
a x .a y = a x+ y
4
(a )
x y
Example for rule of exponent
Let the base a = 2, base b = 4, x = 2 and y = 3
4
ax = a x− y ay
ax a = x b b
a =1
0
=a
xy
a x .a y = a x + y
2 2.2 3 = 2 2 + 3 = 2 5 = 32
(ab )
x
x
=a b
x
x
a −x =
1 ax
ax = a x− y ay
22 1 1 = 2 2−3 = 2 −1 = 1 = 3 2 2 2
a = a
x y
(a )
a =a
1
51
x y
= a xy
= a xb x
(2 )
2 3
= 2 ( 2)(3) = 2 6 = 64
y
x
(ab ) x
(2 x 4) 2 = 2 2 x 4 2 = 4 x16 = 64
52
Example for rule of exponent
Let the base a = 2, base b = 4, x = 2 and y = 3
4
Logarithmic Function
5
a a = x b b 1 −x a = x a
x
x
x
2 4 1 2 = = 2 = 4 16 4 4 1 1 2 −2 = 2 = 4 2
2
2
2
a y = ax
a0 = 1 a1 = a
y
2 3 = 3 22 = 3 4
20 = 1
The logarithmic function with base b, where b > 0 and b ≠ 1, is defined by logb and is defined by y = logbx if and only if by = x The domain of logb is all positive real numbers and the range is all real numbers. y = logbx means by = x
53 54
21 = 2
Logarithmic Function
5
Example: Converting from Exponential 5 to Logarithmic Form
Exponential Form a. Since b. Since c. Since 52 = 25 34 = 81 100 = 1 then then then Logarithmic Form Log5 25 = 2 Log3 81 = 4 Log10 1 = 0
In this sense, a logarithm of a number is an exponent: logbx is the power to which we must raise b to get x. Example:
logarithm exponent
Log28 = 3
because 23 = 8
base
55 56
Example: Converting from Logarithmic 5 to exponential Form
Logarithmic Form Exponential Form
Original Logarithmic
2 type of log function, with base 10 and e: log10 x written as log x loge x written as ln x
5
a. Log10 1000 = 3 b. Log64 8 =
1
means means means
103 = 1000
1
1 2
64 2 = 8
c. Log2 16 =  4
2 4 =
1 16
57 58
Rule of Logarithmic
a log a N = N log a a = 1 log a 1 = 0 log a ( MN ) = log a M + log a N
5
Exponential Equations
There 2 way to solve exponential equation:
5
M log a = log a M − log a N N log a M p = p log a M log a x log b x = log a b If log a x = log a y then x = y
writes both left hand side and right hand side of equation in the same bases and then compared and solved writes both left hand side and right hand side of equation in the logarithmic equation
59 60
Exponential Equations
Example: Solve 8 x 1 8 x 1 = 1 32 x 1 25x
 5x
5
Logarithmic Equations
5
1 32 x
=0
then : 3x  3 =  5 x 3x + 5 x = 3 8x = 3
Logarithmic Equation is solve by writing both left hand side and right hand side of equation in the same bases
(2 3 ) x 1 = 2
3x  3
= 2
(same base which is 2)
x=
3 8
61
62
Logarithmic Equations
Example: Solve 2 log 2 y = 2 + log 2 ( y  1)
2 log 2 y = 2 + log 2 ( y  1) 2 log 2 y  log 2 ( y  1) = 2 log 2 y  log 2 ( y  1) = 2 log 2 y =2 ( y  1)
2 2
5
y2 = 22 ( y  1)
y 2 = 4( y  1) y 2 = 4y  4 y 2  4y + 4 = 0 (y2) (y2) = 0 y= 2
63
This action might not be possible to undo. Are you sure you want to continue?
We've moved you to where you read on your other device.
Get the full title to continue reading from where you left off, or restart the preview.